2009
DOI: 10.1111/j.1600-0528.2009.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and serum albumin change after prosthodontic treatment among institutionalized elderly in a long‐term care geriatric hospital

Abstract: It can be concluded that prosthodontic treatment may improve the nutritional status of institutionalized elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…We also observed a nonsignificant increase in the values of serum albumin in patients who received prosthodontic treatment. Our results were in correlation with the results obtained by Kanehisa et al 16 who also observed an increase in serum albumin values in denture users.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also observed a nonsignificant increase in the values of serum albumin in patients who received prosthodontic treatment. Our results were in correlation with the results obtained by Kanehisa et al 16 who also observed an increase in serum albumin values in denture users.…”
Section: Discussionsupporting
confidence: 93%
“…While comparing the mean change in the nutritional parameters in the patients who underwent different treatment modalities, we observed significant improvement in body weight and BMI in the group of patients who received CD compared with patients who received RPD and FPD, as shown in Table 3. Kanehisa et al 16 observed similar results in their study, in which they found significant increase in mean body weight between denture wearers and nonwearers. The possible reason for this increase in mean body weight may be because of the improvement in mastication due to denture wearing and increased comminution and nutrient absorption from gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Conversely Wöstmann et al 21 (2008) observed enhancement in the nutritional conditions of individuals in relation to adequacy of the dentures, a fact verified by mini evaluation of the nutritional status and determination of the blood levels of albumin and zinc. Kanehisa et al 22 (2009) also found higher levels of serum albumin for individuals who used partial dentures compared with non-users six months after prosthodontic treatment. De Marchi et al 10 (2010) and Tsakos et al 20 (2010) found greater fruits and vegetables intake in dentate or denture users elderly in comparison to edentulous.…”
Section: Resultsmentioning
confidence: 98%
“…The improvement of dentures benefits the masticatory ability with positive impact on the nutritional status 21 , increasing body weight and albumin level 22 without changes on intake of energy and nutrients 23 . Moreover, the treatment with implanted-supported dentures can modify the function of stomatognathic system 24 and the nutritional status of edentulous elderly individuals, thus enhancing their anthropometric 25 and biochemical evaluation 26 .…”
Section: Introductionmentioning
confidence: 99%